2022
DOI: 10.2478/bioal-2022-0080
|View full text |Cite
|
Sign up to set email alerts
|

A double photon coincidence detection method for medical gamma-ray imaging

Abstract: Cascade nuclides emit two or more gamma rays successively through an intermediate state. The coincidence detection of cascade gamma rays provides several advantages in gamma-ray imaging. In this review article, three applications of the double photon coincidence method are reviewed. Double-photon emission imaging with mechanical collimators and Compton double-photon emission imaging can identify radioactive source positions with their angular-resolving detectors, and reduce the crosstalk between nuclides. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…While the means for distinguishing between prompt and annihilation gamma ray signals may be feasible based on these findings, development of such a technique constitutes future work. We have demonstrated eventby-event discrimination based purely on ∆ϕ filtering yields poor but better than nothing classification results, as expected [26]. Despite this, Kim et al has recently demonstrated an in increase to signal-to-noise ratio in reconstructed images based solely on ∆ϕ filtered coincidence data [28].…”
Section: Discussionsupporting
confidence: 77%
“…While the means for distinguishing between prompt and annihilation gamma ray signals may be feasible based on these findings, development of such a technique constitutes future work. We have demonstrated eventby-event discrimination based purely on ∆ϕ filtering yields poor but better than nothing classification results, as expected [26]. Despite this, Kim et al has recently demonstrated an in increase to signal-to-noise ratio in reconstructed images based solely on ∆ϕ filtered coincidence data [28].…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, this kind of cascade gamma emission has also been discussed for effective use as multi-photon imaging. 23,24) While the use of 124 I for o-Ps lifetime imaging would seem to be challenging, we focused on this radionuclide as it has been studied for such applications as dosimetry in 131 I thyroid cancer treatment, 25,26) imaging of various in vivo cancer tumors, 27) and immunoPET imaging using tumorspecific antibodies. 28,29) No report has appeared on the use of 124 I for o-Ps lifetime imaging as far as we know.…”
mentioning
confidence: 99%